Mitochondrial Protein Synthesis Adapts to Influx of Nuclear-Encoded Protein - Richter-Dennerlein, Ricarda; Oeljeklaus, Silke; Lorenzi, Isotta; Ronsör, Christin; Bareth, Bettina; Schendzielorz, Alexander Benjamin; Wang, Cong; Warscheid, Bettina; Rehling, Peter; Dennerlein, Sven (Cell, 2016)
Mitochondrial ribosomes translate membrane integral core subunits of the oxidative phosphorylation system encoded by mtDNA. These translation products associate with nuclear-encoded, imported proteins to form enzyme complexes that produce ATP. Here, we show that human mitochondrial ribosomes display translational plasticity to cope with the supply of imported nuclear-encoded subunits. Ribosomes expressing mitochondrial-encoded COX1 mRNA selectively engage with cytochrome c oxidase assembly factors in the inner membrane. Assembly defects of the cytochrome c oxidase arrest mitochondrial translation in a ribosome nascent chain complex with a partially membrane-inserted COX1 translation product. This complex represents a primed state of the translation product that can be retrieved for assembly. These findings establish a mammalian translational plasticity pathway in mitochondria that enables adaptation of mitochondrial protein synthesis to the influx of nuclear-encoded subunits.